Needs Analysis of Electronic Student Worksheets (E-LKM) Based on Project-Based Learning (PJBL) in Introduction to Metabolism Material - Fatmawati, Fatmawati (Biopedagogia, 2024)
This research aims to determine students' needs for electronic student worksheets (E-LKM) based on project-based learning on introductory metabolism material. This research is descriptive. The subjects of this research were students of the Biology Education study program at the Faculty of Teacher Training and Education class of 2021. Data was collected using observations of the Biochemistry lecture process and interviews. Based on the results of observations of eight aspects which are essentially contained in three indicators. These indicators are digital media needs analysis, material analysis, and analysis learning methods. Based on research results related to digital media, it is known that students rely on smartphones in the learning process, student interaction with smartphones is quite high, and students need flexible, open material with clear guidelines. This shows that open material in digital form can be easily accepted by students. Based on material analysis, Biochemistry material still tends to be considered as material that is difficult to understand, whereas in Biochemistry material there are topics that have the potential to be applied in projects. Based on the learning analysis method, the learning method applied is discussion and question and answer using PowerPoint and students have never used worksheets on Biochemistry material. This shows that learning methods are needed that can help students understand the concepts of the material. It can be concluded that project-based Electronic Student Worksheets (E-LKM) need to be developed in the learning process